Excitable systems: A new perspective on the cellular impact of elongate mineral particles - Shuyao Gu; Abby Bull; Jeneh K. Perry; Amilee Huang; Matt J. Hourwitz; Mona Abostate; John T. Fourkas; Andrey A. Korchevskiy; Ann G. Wylie; Wolfgang Losert (Environmental Research, 2023)

Natural variation in the contribution of microbial density to inducible immune dynamics - Derrick Jent; Abby Perry; Justin Critchlow; Ann T. Tate (Molecular Ecology, 2019)
Immune responses evolve to balance the benefits of microbial killing against the costs of autoimmunity and energetic resource use. Models that explore the evolution of optimal immune responses generally include a term for constitutive immunity, or the level of immunological investment prior to microbial exposure, and for inducible immunity, or investment in immune function after microbial challenge. However, studies rarely consider the functional form of inducible immune responses with respect to microbial density, despite the theoretical dependence of immune system evolution on microbe‐ versus immune‐mediated damage to the host. In this study, we analyse antimicrobial peptide (AMP) gene expression from seven wild‐caught flour beetle populations ( Tribolium spp.) during acute infection with the virulent bacteria Bacillus thuringiensis (Bt) and Photorhabdus luminescens (P.lum) to demonstrate that inducible immune responses mediated by the humoral IMD pathway exhibit natural variation in both microbe density‐dependent and independent temporal dynamics. Beetle populations that exhibited greater AMP expression sensitivity to Bt density were also more likely to die from infection, while populations that exhibited higher microbe density‐independent AMP expression were more likely to survive P. luminescens infection. Reduction in pathway signalling efficiency through RNAi‐mediated knockdown of the imd gene reduced the magnitude of both microbe‐independent and dependent responses and reduced host resistance to Bt growth, but had no net effect on host survival. This study provides a framework for understanding natural variation in the flexibility of investment in inducible immune responses and should inform theory on the contribution of nonequilibrium host‐microbe dynamics to immune system evolution.

Erratum to: Civil society research and Marcellus Shale natural gas development: results of a survey of volunteer water monitoring organizations - Kirk Jalbert; Abby J. Kinchy; Simona L. Perry (Journal of Environmental Studies and Sciences, 2014)

Civil society research and Marcellus Shale natural gas development: results of a survey of volunteer water monitoring organizations - Kirk Jalbert; Abby J. Kinchy; Simona L. Perry (Journal of Environmental Studies and Sciences, 2014)